Soft-sediment deformation structures related to tectonomagmatic activity: A case study from the borate-bearing lacustrine deposits of early Miocene Bigadic Basin, NW Turkey - Koc-Tasgin, Calibe; Diniz-Akarca, Cansu (Elsevier Science Bv, 2018)
This study documents soft-sediment deformation structures in the lacustrine Bigadic Basin, one of the early Miocene terrestrial basins in the extensional tectonomagmatic province of northwestern Anatolia. The focus is on the Upper Borate Unit of the basin-fill succession, which consists of sedimentary facies including massive conglomerates, stratified sandstones, siltstones, organic-rich claystones, laminated limestones, organic-rich limestones, marlstones, borates and volcaniclastics. Their deposition, including borates, occurred in a deep lacustrine environment. Possible phases of lake shallowing are represented by stratified sandstones facies. Soft-sediment deformation features include small-scale folds formed by convolution with occasional basal decollement (minor slumps); load casts and related flame structures; fragmented and mixed beds, brecciated by pore-water explusion; shallow-and deep-rooted synsedimentary extensional faults with related neptunian dykes; and large slump sheets of thick bed packages with recumbent folds. These deformation features are interpreted to be of seismo-tectonic and seismo-volcanic origin, related to syndepositional strike-slip faulting and volcanic eruptions. Seismic tremors combined with the basin floor updoming by magma intrusions caused deep-rooted normal faults and intra-basinal slumps tens of metres thick. The study may serve as a guide to similar deformation structures in the underlying part of the Bigadic lake-fill succession and in the other Neogene basins of northwestern Anatolia-which shared the region's seismo-tectonic, magmatic, palaeogeographic and sedimentation history. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Seismites; Slumps; Palaeolake; Lithofacies; Volcanism; Anatolia